Evaluation of Liver Metabolism Biomarkers in Metabolic Associated Fatty Liver Disease According to Obesity Phenotype. Issue 2 (17th February 2023) - Loureiro, Ligiane M; Cordeiro, Adryana; Barboza, Letícia; Mendes, Rodrigo; Pereira, Sílvia; Saboya, Carlos J; Ramalho, Andrea
Abstract: Objective: To analyze the relationship between the biochemical markers of liver metabolism in different stages of Metabolic Associated Fatty Liver Disease (MAFLD) according to the obesity phenotype. Methodology: This is a cross-sectional study with individuals with class III obesity classified according to the obesity phenotypes proposed by the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria. Biochemical and anthropometric variables were analyzed according to the staging of MAFLD and obesity phenotype. Results: A total of 50 subjects with MAFLD, 62% (n = 31) with steatosis and 38% (n = 19) with steatohepatitis without fibrosis; 36% were classified as metabolically healthy obesity (MHO) and 64% as metabolically unhealthy obesity (MUHO), respectively. Mean values of alkaline phosphatase were 85.44 ± 27.27 vs. 61.92 ± 17.57 ( p = 0.006); gamma-glutamyl transpeptidase, 25.77 ± 15.36 vs. 30.63 ± 19.49 ( p = 0.025); and albumin, 3.99 ± 0.34 vs. 4.24 ± 0.23 ( p = 0.037), were lower and statistically significant in the MHO group with steatosis. The results show when considering individuals with IR, only AP is a predictor of unhealthy phenotype (B-0.934, 0.848- 1.029, p = 0.031). Conclusion: MHO individuals with steatosis present lower severe changes related to markers of liver damage and function and AP is considered the predictor of MUHO phenotype.